Risk Factors for Obesity un Adolescents from the Tulcán Popular Housing Neighborhood - Mayra Jeaneth Jiménez Jiménez (Revista Finlay)
Foundation: obesity is caused by multiple factors that can significantly affect people's lives, causing serious health problems and diseases such as hypertension, diabetes and dyslipidemia, among others. Objective: to describe the risk factors causing obesity in adolescents from the popular housing neighborhood of Tulcán, Ecuador. Methods: a descriptive study was carried out for the period from January to December 2023. The sample size consisted of 179 subjects. The variables were analyzed: frequency of reviewing the caloric value of foods, frequency of meals, feeling when eating, type of sport, liquid for hydration, activity during the day and type of food consumed at home. Within the statistical analysis, absolute and relative frequencies were used as summary measures. Results: the 63 % of those surveyed reported that they only sometimes looked at the calories of the foods they consumed. The 57 % reported eating between 2 and 4 times a day. The 54 % reported eating more food when they felt sad. The 29 % did not do any sport. The 34 % ate French fries and 8 % ate hamburgers. Conclusions: the following were described as risk factors that led adolescents to obesity: socioeconomic conditions, high consumption of calories and micronutrients, ingestion of food at inappropriate times and more times than normal, insufficient levels of physical activity, and consumption of high consumption of sugary drinks and processed foods.